Application of seismic attributes in structural and facies modeling for volume calculation on statjford formation, notrh viking graben. Issue 1 (March 2021) - Aji, W P; Haris, A; Ajar, S B
Abstract: Viking Graben is the dominant main structure in the northern North Sea. The study area is located on North Viking Graben. In this study focused on the formation of Statfjord. The formation was precipitated during the late Triassic until the early Jurassic. This layer is a sandstone sediment. The reservoir characterization of the coating will be done by integration of seismic attribute analysis and seismic inversion. Seismic attribute analysis is performed to identify the boundary layer, which is indicated by the difference between the two layers and the inversion seismic done to show the acoustic impedance which is useful to know the characteristics of the layer. Both attributes (seismic amplitude and acoustic impedance) are expected to investigate the complete reservoir. Based on the results of interpretation and analysis of the seismic attribute will be built geological model as a basis for treating reservoir volume calculations by volumetric methods. In this research, the results obtained in the form of porosity distribution map with a large porosity value of 0.125 - 0.225 (%) and STOIIP distribution map with a large reservoir volume of 186 × 106 sm3